Juan Calvino's contributions to education. Review - Aponte Lopez , Andres Camilo (Multidisciplinar (Montevideo), 2023)
This article presents a systematic review of the literature from the last 10 years on the contributions of John Calvin to education from the perspective of Reformed theology. It was developed in four sections: a biography of Calvin, Calvin's Geneva, the schools in Geneva, and the impact of Calvin on education. The results show that Calvin's contributions to Christian and universal education were enduring, his emphasis on Bible-based teaching, and his vision involving the home, school, and church. This study highlights the relevance of Calvin's educational principles and their impact on current education